Sports Marketing An Australian Perspective - Richards, Jessica (Open textbook library., 2024)
Sports marketing refers to promoting goods and services through sporting events and the endorsement of athletes and sports teams. For any sports organisation, it is imperative to have an effective sports marketing strategy in place to build brand awareness, enhance customer loyalty and generate revenue. Companies in sports use marketing strategies to fulfil their goals, such as attracting more junior players, involving parents, increasing the company's public profile, entertaining spectators, acquiring sponsorships, and securing broadcasting rights deals. This book has been written for sports management students at Western Sydney University for the subject Sports Marketing (BUSM2048) where they will learn general marketing knowledge and theories relevant to the sports industry, such as sponsorship, endorsements, customer experience, pricing and operations. This activity is aligned with SDG4 – Quality Education.